Stingless bee keeping: Biocultural conservation and agroecological education - Aldasoro Maya, Elda Miriam; Rodríguez Robles, Ulises; Martínez Gutiérrez, María Luisa; Chan Mutul, Guelmy A.; Avilez López, Teresita; Morales, Helda; Ferguson, Bruce G.; Mérida Rivas, Jorge A. (Frontiers in Sustainable Food Systems, 2023)
Stingless bee breeding, also called Meliponiculture, has existed for thousands of years in Mesoamerica among a variety of rural and indigenous cultures. Due to its biocultural importance, it represents a perfect device for agroecological education and scaling, as well as pollinator conservation. At the same time, promoting agroecological transitions are necessary for conserving the cultural heritage that meliponicultures represent. We organized a series of activities based on this premise: documenting and dialoguing “saberes contemporáneos” (contemporary knowledges), design and implementation of community agroecological workshops, guided visits at the institutional Meliponary at ECOSUR Villahermosa and promotion of agroecological and biocultural school gardens, all in Tabasco, México. We used “diálogo de saberes” (knowledge dialogues) as a methodological approach, promoting respect for the contribution of the diversity of ontoepistemologies involved. We drew on the ideas of several pedagogues, mainly from popular education and critical pedagogy frameworks. We identified characteristics of stingless bees and meliponicultures that make them excellent mediators for biocultural conservation and agroecological education: the complex, deep and beautiful relation between humans and bees; meliponiculture’s ecological and cultural importance; stingless bees as pollinators par excellence, landscape connectors, and charismatic species; the association of bees with values around work and community; meliponicultures’ symbolic relevance and emotional significance; meliponicultures as promoters of intergenerational dialogue; bee keeping as an activity of caring for the continuity of life; sensory stimulation through contact with colonies; learning through doing in the practice of beekeeping; meliponicultures as an activity requiring skill but no special equipment; and meliponiculture’s productive potential. This confluence of teaching-learning opportunities, cultural and moral values, care for the land and biocultural diversity, and economic potential makes meliponiculture a potent catalyst for agroecological learning and transitions.